International marketing strategy : analysis, development and implementation / Isobel Doole, Robin Lowe. - Doole, Isobel, 1954-; Lowe, Robin, 1945- (London : Cengage Learning, 2008)
This text looks at context, techniques and strategies involved in successful international marketing. It sets out to provide a good balance of the theory and implementation behind international marketing.
Previous ed. : 2004.
Includes bibliographical references and index.
Keywords: Export marketing -- Management; Export marketing -- Management -- Case studies; Export marketing -- Management -- Case studies